Analisis kemiskinan orang tua terhadap motivasi belajar anak di Kampung Topeng - Andini, Lilia Ais; Nazhifah, Salsabila Al Mufidatun (Maliki Interdisciplinary Journal, 2024)
This research analyzes of parental poverty on children’s learning motivation in Kampung Topeng. Poverty, defined as the economic inability to achieve a decent standard of living, affects various aspects of life, including education. This research uses a qualitative method with a descriptive approach, collecting data through observation and interviews with two children from poor families in Kampung Topeng. The results show that parental poverty has a significant impact on children’s learning motivation. Children from poor families often have to help earn a living, which can reduce their time and energy for learning. Difficult economic conditions also cause stress and psychological pressure that can reduce children’s motivation to learn. These findings highlight the need for comprehensive interventions, including skills training programs and improved access to education and health services, to break the cycle of poverty and increase children’s motivation to learn. Psychological support and career guidance are also important to boost children’s confidence and motivation to continue their education.